PERUBAHAN TEKSTUR KERUPUK BERPATI AKIBAT SUHU DAN LAMA PENYANGRAIAN - Irmayanti, Irmayanti; Syam, Husain; Jamaluddin P, Jamaluddin P (Jurnal Pendidikan Teknologi Pertanian, 2017)
The texture on the food consists of smooth and coarse, liquid and solid, hard and mushy. Texture greatly affects the food that can be felt with pressure and movement of the receptor in the mouth. One type of food that relies on texture is crackers. The purpose of this study is to analyze the texture changes in the crackers to the temperature and time used. The temperature used is 120OC, 140OC and 160OC with variation of time ie 10, 15, 20 and 25 seconds. The measured parameters were hardness and organoleptic test result of texture. The best crackers in terms of texture is a cracker that uses temperature 140OC with time 25 seconds and 160OC with time 20 seconds